Russian Old Believers in Latin America - D. V. Belov (Ибероамериканские тетради)
In the 1950s and 1960s, over 300 families of Russian Old Believers left their country’s Far East region to move first to China and later to Latin America, fleeing mainly to Brazil and Argentina to escape persecution once the collectivization began in the Soviet Union. Subsequently, some of the families settled in Bolivia, Chile and Uruguay. There is also evidence that Russian Old Believers live in Paraguay. They have preserved their language, cultural identity and religion (Russian Old Believers in Latin America are «Bespopovtsy», meaning they reject priests), which resulted from keeping their communities closed, with their members banned from marrying those of a different faith. Russian Old Believers are engaged in agriculture: they lease fields to grow and sell cereals and legumes typical for the countries where they live, in addition to raising livestock, fishing and hunting. Moreover, Russian Old Believers preserve traditional crafts, such as embroidery, weaving, making lace, coining crucifixes and icons, and their craftsmanship is highly acclaimed. Apparently, Russian Old Believers migrated to Latin America even before mid-20th century, yet the cases were singular, which seemed to have accelerated their assimilation. Some 15 years ago, when «The State Program for Assisting Voluntary Resettlement of Compatriots Living Abroad to the Russian Federation» was launched, several Old Believers returned to their historical homeland. Nonetheless, for a number of reasons, they do not move from Latin America to Russia on a massive scale.